Perceived Level of Late Reverberation in Speech and Music - Paulus, Jouni; Uhle, Christian; Herre, Jürgen (130th Audio Engineering Society Convention 2011, 2011)
This paper presents experimental investigations on the perceived level of running reverberation in various types of monophonic audio signals. The design and results of three listening tests are discussed. The tests focus on the influence of the input material, the direct-to-reverberation ratio (mixing level), and the reverberation time using artificially generated impulse responses for simulating the late reverberation. Furthermore, a comparison between mono and stereo reverberation is conducted. It can be observed that with equal mixing levels, the input material and the shape of the reverberation tail have a prominent effect on the perceived level. The results suggest that mono and stereo reverberation with identical reverberation times and mixing ratios are perceived as having equal level regardless of the material.
CRIS-Team Scopus Importer:2023-02-20